MENEPIS PRASANGKA DAN DISKRIMINASI DALAM PERILAKU BERAGAMA UNTUK MASA DEPAN MULTIKULTURALISME DI INDONESIA - Triana Rosalina Noor (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2020)
Indonesia is a multicultural nation that has a variety of ethnic, racial, cultural, linguistic, and religious diversity. This diversity makes its challenges in creating a harmonious society. This is because it can bring some people trapped prejudice and discrimination, especially in religion. The prejudice that leads to discrimination and acts of violence will make social conflicts more acute in the multidimensional crises that occur in Indonesia.This article aims to describe prejudice and discrimination behavior from an individual psychological perspective, sociological, and cultural background. Besides that, it was also explained the idea of how to prevent and overcome prejudice and discrimination in religious beliefs that occurred. Efforts to prevent prejudice and discriminatory behavior in religion can be done by increasing the value of the group that is prejudiced, opening communication, conditioning the environment to internalize social norms. The hope is that all citizens can live side by side and respect each other in a peaceful and peaceful atmosphere.